9. ANALISIS POLA PENYELUNDUPAN SENJATA ILEGAL: STUDI KASUS POLA PENYELUNDUPAN SENJATA OLEH VIKTOR BOUT DI ANGOLA DAN LIBERIA TAHUN 1990-1998 - M Yaser Arafat; Tri Cahyo Utomo; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The notorious Viktor Bout, the most influenced person in the illegal arms smuggling hashuge reputation in supplying illegal arms to the conflicted countries. With his offshorecompanies and his wide-scale network in arms business he supplied small arms and lightweapon (SA/LW) freely without any suspicion of violated the arms embargoes. Liberiaand Angola were countries which clearly cooperated with Viktor Bout to illegally sellarms with the high intensity. Using the method of library research, arms traffickingconcept, and refer to the previous research also with the comparison method in the patternused by Bout in both countries, this research concludes that there is opposite pattern inarms smuggling between Liberia and Angola by Bout. In his operation in Liberia, Boutused the pattern of government assisted-trade which he used to cooperate with localgovernment to illegally break arms embargo and smuggle arms. In Angola, he used thepattern of company brokered-trade which allowed him to utilize his companies andcooperation network to help him smuggled arms to both government and rebel group inAngola.